US-Latin American economic relations. - WEINTRAUB, Sidney (1997)
Is of the view that US relations with Latin America deserve a higher priority in US thinking than they have been given in recent years. Further, the change in the Latin American development model from protected markets and export pessimism to increasing openess to foreign investment and imports, and more thorough penetration of foreign markets, has stimulated open regionalism. Recommends that the US (1) provides fast-tract authority for hemispheric trade negotiations; and (2) proposes a schedule for meeting the Miami Summit timetable to complete the FTAA negotiations by 2005.